HB-HTA as an implementation problem in Polish health policy. - Małgorzata Gałązka-Sobotka (Public Library of Science (PLoS), 2021)
Hospital Based Health Technology Assessment (HB-HTA) is a new policy implemented in Poland to allow for a more practical and contextualized assessment related to the use of specific medical procedures, devices, or equipment. It requires changes in governance relating to the healthcare sector. One of the forms of governance improvement is to involve society in the process of creating public services. This can be implemented, e.g., by applying the pragmatic model of public responsiveness. The aim of this research was to identify and analyze forces which will shape a dynamic process in determining the implementation of HB-HTA. The results obtained in the Gioia analysis led to the identification of the main forces driving and restraining the implementation of HB-HTA. The grouping and interpretation allowed for the twelve most important dimensions to be distinguished, which were recognized as conceptual categories necessary to build theories that describe the studied phenomenon. This study contributes to the development of the idea of responsiveness in public management theory and in health care services, and ultimately helps to better enable the adjustment of health services to the dynamically changing needs of Polish society.